PENGARUH KREDIT BERMASALAH/NON PERFORMING LOAN DAN SUKU BUNGA SERTIFIKAT BANK INDONESIA TERHADAP PERKEMBANGAN VOLUME KREDIT PERBANKAN DI INDONESIA - Dewi, Anita Kusuma (Jurnal Manajemen Magister Darmajaya, 2015)
The purpose of this study was to analyze factors that influence the development of bank credit at commercial banks in Indonesia which consists of variables, Non-performing loans and the interest rate of Bank Indonesia Certificates. The model used in this study is the Error Correction Model by using secondary data of monthly time series data.These results indicate that there is a relationship between the dependent variable credit with two independent variables in both the short and long term, the relationship between independent variable NPL/Non Performing Loan and SBI/The Interest rate of Bank Indonesia Certificates are positively effected by dependent variable volumes of credit at commercial banks in Indonesia.Non Performing Loan variable has positive and significant impact at long-term positive related but not significant in the short-termwhile variable SBI/the interest rate of Bank Indonesia Certificateshas positive and significant impact on the volume of commercial bank credit in Indonesia. Â Keywords: Total Loans, Non Performing Loans, The Interest rate of Bank Indonesia Certificates